Higgs boson coupling sensitivity at the LHC using H -> tau tau decays - Boddy, C; Farrington, S; Hays, C (2012)
We investigate the potential for measuring the relative couplings of a low-mass Higgs boson at the Large Hadron Collider using WH, ZH, and tt̄H production, where the Higgs boson decays to tau-lepton pairs. With 100fb -1 of √s=14TeV pp collision data we find that these modes can improve sensitivity to coupling-ratio measurements of a Higgs boson with a mass of about 125GeV/c2. © 2012 American Physical Society.